Formulating SMART Learning Objectives in EFL Curriculum: A Qualitative Literature Review - Helli Ramdanniah Liswati; Nadia Nadia; Ikrimah Ikrimah; Zaitun Qamariah (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This literature review investigates the effectiveness of formulating SMART (Specific, Measurable, Achievable, Relevant, and Time-bound) learning objectives within the English as a Foreign Language (EFL) curriculum using a qualitative research method. A systematic literature review was employed to analyze empirical and theoretical studies published between 2015 and 2024. The findings reveal that SMART objectives contribute to increased instructional clarity, learner engagement, and alignment with curriculum goals. Thematic content analysis highlights key benefits, such as improved learner autonomy, language proficiency, and instructional planning. This study provides a structured synthesis for educators and policymakers in designing effective EFL curricula.